The portfolio theory of inflation (and policy effectiveness) - Biagio Bossone (Kiel Institute for the World Economy (IfW), 2019)
The Portfolio Theory of Inflation (PIT) proposed in this study investigates the role of global financial markets in determining the effectiveness of macroeconomic policy in open and fully financial integrated economies. The PIT adopts a modified version of the portfolio balance approach to exchange rate determination and incorporates intertemporal optimal choices from global investors. These investors allocate resources across national economies based on local investment opportunities and policy credibility: when a country's credibility is low, they hold its economy to a tighter intertemporal budget constraint and the issuance of what they deem as "excess" public sector liabilities causes the country's currency to depreciate and inflation to rise due to a large exchange rate pass-through, with limited or no impact on output. On the other hand, high credibility creates space for effective and noninflationary macro policies but, if such space is abused, credibility gets dissipated and higher inflation reflects such dissipation.
Keywords: E31; E4; E5; E62; F31; G15; H3; 330; credibility; exchange rate; financial integration; global investor; interest rate; intertemporal budget constraint; money; bonds and assets; pass-through